Sosialisasi Pengurangan Sampah Plastik Sekali Pakai untuk Meningkatkan Kesadaran Lingkungan di SMPN 3 XIII Koto Kampar - Erlinda, Sri; Primahardani, Indra; Haryono, Haryono; Rahmatullaila, Fitri (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
The problem of single-use plastic waste is becoming an increasingly serious environmental issue due to the high consumption of plastic in everyday life, including in the school environment. Low awareness and environmentally friendly behavior among students has an impact on increasing plastic waste which causes environmental pollution and health. This activity aims to increase students' environmental awareness through socialization of reducing the use of single-use plastic waste at SMP N 3 XIII Koto Kampar. The implementation method includes three stages, namely preparation, implementation of socialization, and evaluation. The socialization was held on August 22–24, 2025, involving all students, teachers, the principal, and lecturers as resource persons. The methods used in the socialization included lectures, interactive discussions, and questions and answers regarding the impact of plastic waste and the application of the 3R principle (reduce, reuse, recycle). The results of the activity showed an increase in students' understanding and awareness of the negative impacts of single-use plastic waste. In addition, there was a change in attitude demonstrated through students' positive responses to the use of environmentally friendly alternatives such as refillable drinking bottles and non-plastic food containers. This socialization activity has proven effective as an educational effort in raising environmental awareness and encouraging changes in students' behavior towards a more sustainable lifestyle.